Case Study Experiment: A Toolkit to Drive Cultural Change - Lewis, Lorinda Faye (International Journal of Advanced Corporate Learning (iJAC), 2019)
Abstract Both private and public sectors are ready for a new management model that engages the workforce. Necessitated by the baby boomer retirements rates, lower unemployment, an increased demand for skilled and unskilled labor, and the newest generation in the employment pool, companies have a need to create cultures that attract and retain talent like never before. As a result, a variety of new books, articles, and theories have been introduced to the body of knowledge, including concepts to attempt to change the organizational culture. This case study demonstrates an experiment conducted in a Fortune 500 company, integrating theories and practices from a variety of domains to improve the team culture and ultimately business performance. The tools and techniques are offered for replication.